Surface water quality in watersheds dominated by rubber, tea and cardamom plantations in Kerala State, India - Prasannakumari P; Jacob J; Jessy M.D; Pradeep B; Ulaganathan A (International Rubber Conference, 22-24 October 2018, IRRDB, Abidjan, Cote DIvoire. Abstract Handbook. p. 91)
A study was conducted during the period 2015-2017 to investigate the quality of surface water in watersheds dominated by different plantation crops viz, rubber, tea and cardamom in the Western Ghats region of Kerala, India. Watersheds (of about 18-30 km2 area) dominated by selected plantation crops were delineated using survey of India topographic maps, satellite images and field information. Number of sampling locations were 10, 9 and 12 for rubber, tea and cardamom watersheds respectively, depending on watershed area. Water samples were collected during post-monsoon season of 2015, pre-and post-monsoon seasons of 2016 and pre-monsoon season of 2017, and analysed for important physico-chemical parameters using standard protocols. Bacteriological analysis was carried out during the first two sampling seasons. Pesticide residue analysis of selected samples was carried out using GCMS methodology during pre-monsoon season 2017. The study showed that DO was significantly higher in the watershed of rubber compared to tea and cardamom, indicating better health of surface water in rubber system. TDS, total hardness and EC were significantly higher in watersheds of tea and cardamom compared to that in rubber watersheds, possibly due to the higher run off and leaching losses of nutrients into the water bodies. This is substantiated by the significantly higher contents of potassium, calcium, magnesium, sodium and nitrate in watersheds of tea and cardamom compared to rubber. Heavy metal contents were within permissible limits of drinking water in the three watersheds. Bacteriological analysis confirmed the presence of total coliforms and e-coli in all the three watersheds which renders the water unsuitable for drinking purpose. Pesticide residues (organo-chlorines, organo-phosphates and pyrithroides) were below the level of quatification in all the three water sheds. The study provides a comprehensive understanding of surface water quality in the study area.Though the effect of agro-management practices followed in different plantation crops was reflected in the physico-chemical properties of surface water, all these parameters were within the limits specified for drinking water in all the three watersheds.
Keywords: Physico-chemical characteristics; Plantation crops; Surface water; Water quality